Significant Publications on Infectious Diseases Pharmacotherapy in 2016. (October 2018) - Fong, Gary; Skoglund, Erik W.; Phe, Kady; Guastadisegni, Jessica; Shea, Katherine M.; McDaneld, Patrick M.; Perez, Katherine K.; Sofjan, Amelia K.
Purpose: This is a summary of the most important articles on infectious diseases (ID) pharmacotherapy published in peer-reviewed literature in 2016 as selected by clinical pharmacists with ID expertise. Summary: The Houston Infectious Diseases Network (HIDN) was asked to identify articles published in peer-reviewed literature in 2016 that were believed to contribute significantly to ID pharmacotherapy, including human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS). A list of 46 articles on general ID pharmacotherapy and 8 articles on HIV/AIDS were nominated. Members of the Society of Infectious Diseases Pharmacists (SIDP) were surveyed to select 10 general ID articles believed to have made a significant impact on general ID pharmacotherapy and 1 article most significant to HIV/AIDS pharmacotherapy. Of 445 SIDP members surveyed, 212 (47.6%) and 95 (21.3%) members voted for general ID pharmacotherapy- and HIV/AIDS-related articles, respectively. The 11 highest-ranked papers (10 general ID-related articles and 1 HIV/AIDS-related article) are summarized here. Conclusion: With the large number of ID-related articles published each year, it can be challenging to stay current with the most relevant ID publications. This review of significant publications in 2016 may provide a starting point for that process.